Better outcome in pulpotomy on primary molar with Biodentine - Sultana, Asma; Karim, Fahd AA; Sheikh, Md Abdul Hannan; Wahiduzzaman, Mohammad; Alam, Md Shamsul; Hossain, Mahabubul (Update Dental College Journal, 2016)
Aim: The primary objective of any pulp therapy is to maintain the integrity and health of a tooth and its supporting tissue as well as to maintain arch length and space maintenance. The aim of this case is to a probate and popularizes the technique of vital pulpotomy in primary teeth with biodentin. Update Dent. Coll. j: 2015; 5 (2): 57-62